Graphene oxide composite material based on S-doped Co3O4 as well as preparation method and application of graphene oxide composite material
By using S-doped Co3O4 graphene oxide composite material to modify the glass carbon electrode, the problem of high cost and difficulty in operation of precious metal electrode materials is solved, and the rapid, accurate and economical detection of arsenic ions is achieved, which is suitable for a variety of environments.
Patent Information
- Application Number
- CN202510085896.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-29
AI Technical Summary
The prior art When detecting arsenic ions in water, precious metal electrode materials are costly and difficult to operate, and traditional detection methods require advanced instruments and complex sample preparation, which limits their application in on-site analysis.
The S-doped Co3O4 graphene oxide composite material is used as the detection electrode material, and the material is prepared by hydrothermal synthesis method to improve its electrochemical performance, and a high-sensitivity detection electrode is formed by modifying the surface of the glass carbon electrode.
It realizes rapid and accurate detection of arsenic ions, reduces detection costs, and simplifies the operation process. The electrode material has high precision and strong anti-interference, and is suitable for laboratory and on-site environments.
Smart Images

Figure CN119898822A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of water quality detection, and in particular to a composite material based on S-doped Co3O4 graphene oxide, and a preparation method and application thereof. Background Art
[0002] Arsenic contamination in water bodies is a major global challenge that threatens the safety of drinking water in many countries and regions. Once arsenic ions contaminate water or soil, they pose a long-term threat to the environment and human health. The severity of arsenic contamination lies in its widespread presence and difficulty in natural degradation. In some areas, arsenic concentrations exceed safety limits by dozens to hundreds of times. This high concentration of arsenic pollution not only affects water quality, but may also enter the human body through the food chain, causing serious impacts on human health. Long-term drinking of arsenic-contaminated water can lead to a series of health problems, including cancer, cardiovascular disease, and neurological diseases. Therefore, the detection of arsenic ions is crucial to safeguard human health and environmental safety. By promptly identifying and treating water arsenic contamination, we can effectively reduce the harm of arsenic pollution to human health.
[0003] Traditional techniques for detecting arsenic ions include atomic emission spectroscopy, atomic fluorescence spectroscopy, x-ray fluorescence spectroscopy, and biosensor methods. These traditional detection methods require advanced instruments, complex sample preparation schemes, expensive maintenance, and skilled personnel, which makes them less practical for routine field analysis. Electrochemical detection has higher sensitivity, field adaptability, and fast and accurate results. The emerging microfluidic detection technology mainly relies on electrochemical principles. Electrochemical detection methods are divided into electrolysis, potentiometric titration, polarography, and voltammetry according to their basic principles and application areas. Square wave voltammetry is known for its unique voltage waveform, which helps to mitigate interference signals, suppress background current, and improve the accuracy of results. Before analysis, a negative voltage enrichment process is usually used to deposit the target ions onto the electrode surface to improve sensitivity. Currently, noble metals (such as gold and silver) are commonly used electrode materials for arsenic detection. In order to solve the problems of high cost and difficult operation of noble metals in electrochemical analysis, researchers are studying alternative, low-cost materials to provide higher stability and economy. Carbon-based materials, including carbon nanotubes and graphene, are widely used to improve the sensitivity and precision of electrochemical analysis due to their excellent conductivity, chemical stability and large specific surface area. In addition, metal oxides, sulfides and various composites are being explored as potential electrode materials to improve the performance of electrochemical detection.
[0004] Graphene is a special electrochemical material with excellent properties and is widely used in the field of electrochemical detection. As a single-layer carbon material, it has stable chemical properties and reduces the sensitivity to environmental influences during detection. Its high conductivity not only improves the sensitivity of electrochemical sensors, but also speeds up the response time. In addition, its surface can be easily chemically modified, allowing for improved interactions with target molecules through functionality, thereby increasing selectivity. As an environmentally friendly electrode material, Co3O4 nanostructures offer excellent performance and stability. However, their limited use as electrode materials is mainly due to their poor conductivity, which is caused by their semiconductor properties, and therefore, there is a need to enhance their conductive properties. Summary of the invention
[0005] The purpose of the present invention is to provide a composite material based on S-doped Co3O4 graphene oxide and its preparation method and application, which can improve the electrochemical performance of transition metal oxides by doping S. The method will provide strong support for the rapid and accurate detection of arsenic ions, and help to protect human health and environmental safety.
[0006] In one aspect of the present invention, the present invention provides a method for preparing a composite material based on S-doped Co3O4 graphene oxide. According to an embodiment of the present invention, the method comprises the following steps:
[0007] S1. Add sodium sulfide to the reaction system of Co3O4 nanocrystals dispersed in water, react for 0.5-1h, transfer the solution to an autoclave, heat at 80-100°C for 22-26h, and wash to obtain S-Co3O4 nanocrystals;
[0008] S2. Add S-Co3O4 nanocrystals to the graphene oxide suspension and mix them, then heat them at 80-100°C for 22-26h, and wash them to obtain a S-doped Co3O4 graphene oxide composite material.
[0009] In addition, the preparation method of the S-doped Co3O4 graphene oxide composite material according to the above embodiment of the present invention may also have the following additional technical features:
[0010] In some embodiments of the present invention, in step S1, the method for preparing Co3O4 nanocrystals comprises the following steps:
[0011] Co(CH3COO)2·4H2O and hexadecyltrimethylammonium bromide are dissolved in an ethylene glycol aqueous solution, and then the reaction mixture is transferred to an autoclave and heated at 180-22°C for more than 10-14 hours; after the reaction is completed, the autoclave is naturally cooled to room temperature, and Co3O4 crystals are obtained by centrifugation. After washing, the Co3O4 crystals are calcined to obtain Co3O4 nanocrystals.
[0012] In some embodiments of the present invention, the ratio of Co(CH3COO)2·4H2O to hexadecyltrimethylammonium bromide is in the range of 1:2-1:2.4; water and ethanol are used for washing; the calcination temperature is 330-350°C, and the calcination time is 3-4h.
[0013] In some embodiments of the present invention, in step S1: the mass ratio of the sodium sulfide and the Co3O4 nanocrystals is 100:38-100:34; and the washing is performed using water and ethanol.
[0014] In some embodiments of the present invention, in step S2: the mass ratio of the S-Co3O4 nanocrystals to graphene oxide is 2.5:1-3.5:1.
[0015] In another aspect of the present invention, the present invention provides a S-doped Co3O4 graphene oxide composite material prepared by a preparation method of a S-doped Co3O4 graphene oxide composite material.
[0016] In another aspect of the present invention, the present invention provides a method for preparing a detection electrode. According to an embodiment of the present invention, the S-doped Co3O4 graphene oxide composite material is dispersed in deionized water to form a S-Co3O4 nanocomposite suspension, the S-Co3O4 nanocomposite suspension is placed at the center of a glassy carbon electrode, the glassy carbon electrode is dried, and the S-Co3O4 nanocomposite adheres to the surface of the glassy carbon electrode to obtain the detection electrode.
[0017] In addition, the method for preparing a detection electrode according to the above embodiment of the present invention may also have the following additional technical features:
[0018] In some embodiments of the present invention, the glassy carbon electrode is polished with alumina powder, then washed with deionized water, dried, and then added with S-Co3O4 nanocomposite suspension; the amount of S-Co3O4 nanocomposite suspension added is 2 Add 1-1.2 μL to the electrode.
[0019] In another aspect of the present invention, the present invention provides a detection electrode prepared by the preparation method of the detection electrode.
[0020] In another aspect of the present invention, the present invention proposes that the detection electrode is used to detect the concentration of arsenic ions in a water environment.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] 1) Doping with S element improves the electrochemical properties of Co3O4 nanocomposites. The materials prepared by hydrothermal synthesis method have high purity and good dispersibility.
[0023] 2) During the preparation process, the detection electrode of the present invention uses recyclable materials, which reduces pollution to the environment.
[0024] 3) Due to the characteristics of high precision, strong anti-interference and easy operation of the detection electrode of the present invention, it is not only suitable for laboratory research, but also can be widely used in environmental monitoring, industrial wastewater treatment, drinking water safety and other fields, providing strong technical support for the effective monitoring of arsenic ions.
[0025] 4) The doping process of the present invention preserves the basic layered structure of graphene oxide. These mesoporous two-dimensional (2D) nanosheets have a large surface area, allowing the incorporation of many catalytically active sites. 2 The destruction of the bond network makes graphene oxide an electrical insulator, but its abundant oxygen functional groups can restore the π network, thereby improving conductivity. This achieves the effect of high sensitivity and low detection limit of the electrode, as well as strong anti-interference ability. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 Flow chart of the sensor constructed by the glassy carbon electrode modified with the S-Co3O4 nanocomposite material in Application Example 1 of the present invention for detecting As(III);
[0027] Figure 2 Current response diagram of the sensor constructed by the glassy carbon electrode modified with S-Co3O4 in Application Example 1 of the present invention, the bare electrode (Bare) in Comparative Example 1, and the glassy carbon electrode modified with Co3O4 in Comparative Example 2;
[0028] Figure 3 A linear fitting diagram of the electron transfer kinetics and cyclic voltammetric scan rate of the sensor constructed by the S-Co3O4 modified glassy carbon electrode in Application Example 1 of the present invention, the bare electrode (Bare) in Comparative Example 1, and the Co3O4 modified glassy carbon electrode in Comparative Example 2;
[0029] Figure 4Schematic diagram of the optimized experimental conditions of the present invention, wherein (a) is a peak current comparison diagram of different buffer solutions in Application Example 3, (b) is a peak current comparison diagram of different pH values in Application Example 4, (c) is a peak current comparison diagram of different deposition potentials in Application Example 5, and (d) is a peak current comparison diagram at different deposition times in Application Example 6;
[0030] Figure 5 This is a schematic diagram of the effect of interfering ions in Application Example 2 of the present invention;
[0031] Figure 6 Schematic diagram of the repeatability effect of the detection electrode in Example 2 of the present invention (a) and the detection number diagram (b). DETAILED DESCRIPTION
[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] Example 1
[0034] A method for preparing a S-doped Co3O4 graphene oxide composite material comprises the following steps:
[0035] S1. Dissolve 1 g of Co(CH3COO)2·4H2O and 2.2 g of CTAB in 70 mL of a 6:1 solution of ethylene glycol and water. Then transfer the reaction mixture to a 100 ml Teflon autoclave and heat at 200 °C for 12 h. After the reaction is complete, allow the autoclave to cool naturally to room temperature. Obtain Co3O4 crystals by centrifugation and wash thoroughly with water and ethanol to remove impurities. Finally, calcine the crystals at 350 °C for 3 h to obtain 36 mg of Co3O4 nanocrystals dispersed in 50 ml of water.
[0036] S2. During continuous stirring, 100 mg of sodium sulfide (Na2S) was added to the reaction system. After 30 minutes of reaction, the solution was transferred to a polytetrafluoroethylene autoclave and kept at a constant temperature of 90°C for 24 hours. Subsequently, the resulting product was collected and S-Co3O4 nanocrystals were successfully synthesized through multiple washing steps with water and ethanol. The nanocrystals were freeze-dried. Next, 10 mg of reduced graphene oxide (rGO) was dispersed in 100 mL of distilled water and treated with ultrasound for at least 10 minutes to ensure sufficient and uniform dispersion. Subsequently, 30 mg of S-Co3O4 nanocrystals were added to the graphene oxide suspension, and the mixture was mixed for 30 minutes to promote strong bonding between the two components. Afterwards, the entire mixture was transferred to a Teflon container and heated at 90°C for 24 hours. Finally, it was washed with ethanol several times to remove residual impurities to obtain a S-doped Co3O4 graphene oxide composite material, recorded as S-Co3O4 nanocomposite.
[0037] Example 2
[0038] A method for preparing a detection electrode comprises the following steps:
[0039] S1. Polish the glassy carbon electrode with 1.0μm, 0.3μm, and 0.05μm alumina powder respectively. The glassy carbon electrode used is CHI104 from Shanghai Chenhua Instrument Co., Ltd. with a diameter of 3mm. The electrochemical workstation is configured to work in the voltage range of -0.2V to 0.8V. During this period, a solution containing 5mmol / L K3[Fe(CN)6] and 0.1mol / L KCl is used for cyclic voltammetry testing. If the peak voltage difference of the working electrode is within 80mv, the polished electrode is considered to meet the requirements; otherwise, the polishing process is repeated.
[0040] S2. Rinse the working electrode with deionized water and allow it to dry naturally in a clean environment until there is no moisture on the electrode surface.
[0041] S3, weigh 20mg of the S-Co3O4 nanocomposite prepared in Example 1, disperse it in 10ml of deionized water to form a suspension with a concentration of 2mg / mL. Then the suspension is ultrasonically treated for 10 minutes to ensure the uniform distribution of the S-Co3O4 nanocomposite in deionized water. Use a pipette to place 7μL of the suspension in the center of the pretreated glassy carbon electrode so that the suspension is concentrated in the center. The electrode is placed upright in a clean and dust-free environment and air-dried at room temperature for 10 hours. After all the deionized water evaporates, the S-Co3O4 nanocomposite will adhere to the electrode surface to obtain the detection electrode.
[0042] The detection electrodes were placed in the sterile box for 1, 7 and 14 days. Figure 6As shown, after one day of storage, the peak current measured was 79.2 μA, which is 1% lower than the initial test result. After 14 days of storage, the peak current dropped to 78 μA, with an error of about 2.6%. The deviation was minimal in short-term tests, with good stability and high repeatability. However, after extended storage time, the peak current of the electrode decreased significantly. Therefore, the service life of the electrochemical sensor prepared based on this embodiment should be limited to no more than two weeks.
[0043] Application Example 1
[0044] like Figure 1 As shown in the figure, under appropriate potential, As(III) ions are adsorbed to the surface of the modified electrode and enriched in the modified layer. Under a certain negative potential, the As(III) ions enriched on the electrode surface are reduced to As(0). During the forward scanning potential, the reduced As(III) ions are oxidized and dissolved into the solution, and a current signal is generated. The current signal generated in this step is proportional to the concentration of As(III) ions, so it can be used for quantitative detection.
[0045] Specifically, the method for detecting arsenic ion concentration comprises the following steps:
[0046] (1) Preparation of sensor: A CHI760e electrochemical workstation equipped with a three-electrode system (Shanghai Chenhua Instrument Co., Ltd., China) was used to assemble the sensor. The detection electrode prepared in Example 1 was used as the working electrode, the platinum wire electrode was used as the counter electrode, and the saturated KCl-containing calomel electrode was used as the reference electrode.
[0047] (2) Purchase a 1000 ppb arsenic ion solution, dilute it with deionized water to obtain arsenic ion solutions with concentrations of 10 ppb, 20 ppb, 50 ppb, 75 ppb, 100 ppb, 125 ppb, 150 ppb, 175 ppb, and 200 ppb, respectively; then add acetic acid-sodium acetate buffer with a pH of 6 to dilute it to obtain arsenic ion solutions with concentrations of 1 ppb, 2 ppb, 5 ppb, 7.5 ppb, 10 ppb, 12.5 ppb, 15 ppb, 17.5 ppb, and 20 ppb, respectively.
[0048] (3) First, at a voltage of -0.8 V, using the current time deposition method, using the prepared sensor, the arsenic ions in the arsenic solution obtained in step (2) are converted into arsenic elements, and the arsenic is deposited on the surface of the working electrode for 160 seconds. In the subsequent dissolution process, a peak response current is generated. In order to eliminate the residual arsenic remaining on the electrode surface, desorption is then performed for 160 seconds at a voltage of 0.8 V.
[0049] (4) After the electrodeposition process, the sensor was used to perform square wave voltammetry (SWV) measurements. The experimental parameters of SWV were set as follows: the detection potential was set in the range of -0.6 V to 0.6 V, the incremental potential was finely controlled at 4 mV per step, and the square wave amplitude was set to 25 mV to ensure a clear and stable signal. In addition, a frequency of 40 Hz was selected for efficient and sensitive detection.
[0050] The experimental results show that the sensor works in the linear concentration range of 1 to 20 ppb. When the arsenic ion solution exceeds 20 ppb, although the peak response current continues to rise, the linearity of the response decreases. The sensitivity of the sensor is 4.22 μA / ppb, R 2 The value is 0.998. The detection limit is calculated by the following formula:
[0051] C L =K×S÷m (1)
[0052] In the formula, m is the slope of the fitting curve, indicating sensitivity, and K is the confidence level, which is defined by IUPAC (International Union of Pure and Applied Chemistry) as 3. Therefore, to calculate the detection limit, the standard deviation S of the blank data must be obtained. The formula for calculating the standard deviation is shown below:
[0053]
[0054] Where, X i Represents blank data. In this experiment, blank data refers to the measurement results obtained without adding arsenic ion solution to the buffer solution, while other conditions and methods remain unchanged. X represents the average number of blank data points, and N represents the total number of blank data points. The determined detection limit is about 0.8ppb, which is far below the limit of 10ppb set by the World Health Organization. Other electrode materials are adhered to the glassy carbon electrode according to the method of Example 2, and then the electrode is prepared according to the method of this application example. The same test is performed in the linear range of 1-20ppb after dilution with acetic acid-sodium acetate buffer. The results are shown in Table 1.
[0055] Table 1 Comparison of the performance of arsenic ion electrochemical sensors based on electrodes coated with different materials
[0056]
[0057]
[0058] Compared with the performance of the currently available arsenic ion electrochemical sensors, it can be seen that within the linear range of arsenic ion concentration of 1-20ppb, the sensor has high sensitivity and low detection limit, and its performance is better than the existing arsenic ion electrochemical sensors.
[0059] The repeatability of the sensor assembled with S-Co3O4 / rGO nanocomposite modified electrodes for detecting As(III) was evaluated by repeated deposition and anodic stripping in solution. After each stripping cycle, the glassy carbon electrode was tested in phosphate buffer to prevent the adsorption of residual arsenic on its surface. In the first five experiments, the performance of the sensor was relatively stable and reliable, with a minimum deviation of only 0.8% and a maximum error of no more than 2%. Overall, the sensor assembled with S-Co3O4 nanocomposite modified electrodes has good repeatability and consistency under experimental conditions.
[0060] Application Example 2
[0061] The difference between this application example and application example 1 is that eight common pollutants (Ni 2+ , Pb 2+ 、Zn 2+ 、Co 2+ 、SO4 2- , Cl - Br - ) were used as interfering ions, and the arsenic ion concentration was set to 10 ppb and the interfering ion concentration was set to 100 ppb.
[0062] The influence of various interfering ions on the peak current is as follows Figure 5 As shown. Obviously, the influence of metal cations and anions on the peak current is very small, and the maximum deviation does not exceed 2%. This shows that the sensor assembled based on S-Co3O4 nanocomposite modified electrode has good performance and good selectivity for arsenic ions.
[0063] Comparative Example 1
[0064] The method for detecting arsenic ion concentration is different from that of Application Example 1 only in that: in step (1), the working electrode is a bare glassy carbon electrode, and the arsenic ion concentration is 10 ppb.
[0065] Comparative Example 2
[0066] The method for detecting arsenic ion concentration is different from that of Application Example 1 only in that: in step (1), the working electrode is a glassy carbon electrode modified with Co3O4, and the arsenic ion concentration is 10 ppb. The method for preparing the glassy carbon electrode modified with Co3O4 is different from that of Example 2 in that: the S-Co3O4 nanocomposite material in step S3 of Example 2 is replaced by the Co3O4 nanocrystal prepared in step S1 of Example 1.
[0067] At an arsenic ion concentration of 10 ppb, the performance test results of Example 1 and Comparative Examples 1-2 are as follows:
[0068] (1) Current response curve: Figure 2As shown, the current response curves of the sensors assembled with electrodes of Comparative Examples 1-2 and Application Example 1 (arsenic ion concentration of 20 ppb) are compared, and the response of the electrode modified by doping S nanocomposite material is significantly enhanced. This can be attributed to the formation of high-density active sites and surface defects after the introduction of S. This increases the charge transfer rate and diffusion rate of triiodide. In addition, the composite structure effectively reduces the accumulation of single two-dimensional nanosheets, thereby increasing the exchange current density of S-Co3O4 / rGO and limiting the diffusion current density.
[0069] (2) Scanning rate: The sensors assembled with electrodes of Comparative Examples 1-2 and Application Example 1 (arsenic ion concentration of 20 ppb) were respectively experimented at different scanning rates. The experimental parameters were set as follows: high potential was 1 V, low potential was -1 V, and initial potential was 0 V. Three scanning cycles, with a sampling interval of 0.001 V. The scanning rate range was tested, including 0.01 V / S, 0.02 V / S, 0.03 V / S and 0.1 V / S. The corresponding peak anode currents were recorded, and the relationship between these currents and the square root of the scanning rate was analyzed. In the generated scatter plot, the y-axis represents the peak current, the x-axis represents the square root of the scanning rate, and a linear regression analysis is performed. The resulting image is as shown below. Figure 3 shown.
[0070] (3) Cyclic test: In cyclic voltammetry, the equation that matches the peak current measured at three different electrodes with the square root of the scan rate is shown below.
[0071]
[0072]
[0073] In this case, I P It refers to the maximum anodic current recorded in the cyclic voltammetry test, and V represents the speed of scanning the potential during the test. The fitting curve and equation show that when the cyclic voltammetry test is performed on the electrodes modified with different materials, the anodic peak current increases with the increase of the scanning rate, with a high degree of confidence. It is worth noting that the slope of the fitting curve shows that the slope of the electrode modified with the S-Co3O4 nanocomposite material is the steepest, indicating that the electron transfer rate on its surface is the fastest.
[0074] Application Example 3
[0075] The detection method of arsenic ion concentration, the difference between this application example and application example 1 is that: in step (2), the buffer solution is replaced with 0.1 mol / L phosphate buffer solution (PBS), and the arsenic ion concentration after the buffer solution is diluted is 10 ppb, and the remaining steps and parameters are the same.
[0076] like Figure 4As shown in (a), the peak current of As(III) in acetic acid-sodium acetate solution (arsenic ion concentration of 10 ppb) in Application Example 1 is significantly higher than that in phosphate buffer solution, so acetic acid-sodium acetate solution is selected as the preferred buffer solution.
[0077] Application Example 4
[0078] The detection method of arsenic ion concentration, the difference between this application example and application example 1 is that: in step (2), the pH of the acetic acid-sodium acetate buffer solution is changed, and the arsenic ion concentration after the buffer solution is diluted is 10 ppb, and the remaining steps and parameters are the same. Specifically, the pH of the acetic acid-sodium acetate buffer solution is changed to 3.5, 4.5, 6, and 7 respectively.
[0079] like Figure 4 As shown in (b), when the pH increases from 3.5 to 5.5, the peak response current of the square wave voltammetry continues to rise. However, when the pH value continues to increase to 7, the peak response current begins to decrease. The reason for this phenomenon is that under acidic conditions, arsenic ions are more easily oxidized to more valuable arsenic oxides. When the concentration of acidic components in the buffer is too high, hydrogen bubbles will form on the surface of the glassy carbon electrode. The presence of these bubbles interferes with the deposition process of arsenic ions on the electrode surface. Therefore, the electrode's adsorption capacity for arsenic is reduced, which further affects the peak current response observed in subsequent experiments. When the pH is too high, the solubility of arsenate will decrease. In addition, the activity of the electrode surface is affected, resulting in reduced sensitivity and stability of the electrode.
[0080] Application Example 5
[0081] The detection method of arsenic ion concentration, the difference between this application example and application example 1 is that: in step (3), the deposition potential of the current deposition method is changed, and the arsenic ion concentration after the buffer solution is diluted is 10 ppb, and the other steps and parameters are the same. Specifically, the deposition potential is modified to -0.5V, -0.6V, -0.7V, -0.8V, -1.0V.
[0082] like Figure 4 As shown in (c), as the deposition potential increases, the peak current first increases and then decreases. The peak is observed at a deposition potential of -0.8V. Below this potential, the deposition rate on the electrode is too slow, resulting in insufficient deposition. If the deposition potential exceeds -0.8V, the electrochemical reaction on the electrode surface will be intensified, and bubbles may be formed, which will have a negative impact on the deposition of arsenic ions. Therefore, in order to ensure the efficient deposition of arsenic ions, the optimal deposition potential was determined to be -0.8V.
[0083] Application Example 6
[0084] The detection method of arsenic ion concentration, the difference between this application example and application example 1 is that: in step (3), the deposition time of the current deposition method is changed, and the arsenic ion concentration after the buffer solution is diluted is 10 ppb, and the other steps and parameters are the same. Specifically, the deposition time is changed to 120s, 140s, 180s, and 200s.
[0085] like Figure 4 As shown in (d), as the deposition time increases, the peak response current of the electrode detecting arsenic ions also increases. However, the response current increase from 120 to 160 seconds is significantly greater than that from 160 to 200 seconds. The equilibrium between the deposition and desorption of arsenic ions on the electrode surface reaches a state similar to relative saturation. In addition, the extended deposition time enhances the peak current signal, but at the same time increases the thickness of the coating on the glassy carbon electrode surface. This thickening not only hinders the subsequent desorption of arsenic ions, but also reduces the sensitivity of the sensor.
[0086] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the present invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A method for preparing a S-doped Co3O4 graphene oxide composite material, characterized in that: The following steps are involved: S1. Add sodium sulfide to the reaction system of Co3O4 nanocrystals dispersed in water, react for 0.5-1h, transfer the solution to an autoclave, heat at 80-100°C for 22-26h, and wash to obtain S-Co3O4 nanocrystals; S2. Add S-Co3O4 nanocrystals to the graphene oxide suspension and mix them, then heat them at 80-100°C for 22-26h, and wash them to obtain a S-doped Co3O4 graphene oxide composite material.
2. The method for preparing a S-doped Co3O4 graphene oxide composite material according to claim 1, characterized in that: In step S1, the method for preparing Co3O4 nanocrystals comprises the following steps: Co(CH3COO)2·4H2O and hexadecyltrimethylammonium bromide are dissolved in an ethylene glycol aqueous solution, and then the reaction mixture is transferred to an autoclave and heated at 180-220°C for 10-14 hours; after the reaction is completed, the autoclave is naturally cooled to room temperature, and Co3O4 crystals are obtained by centrifugation. After washing, the Co3O4 crystals are calcined to obtain Co3O4 nanocrystals.
3. The method for preparing a S-doped Co3O4 graphene oxide composite material according to claim 2, characterized in that: The mass ratio of Co(CH3COO)2·4H2O to hexadecyltrimethylammonium bromide is 1:2-1:2.4; The washing adopts water and ethanol; The calcination temperature is 330-350° C., and the calcination time is 3-4 hours.
4. The method for preparing a S-doped Co3O4 graphene oxide composite material according to claim 1, characterized in that: In step S1: The mass ratio of sodium sulfide to Co3O4 nanocrystals is 100:38-100:34; The washing is carried out using water and ethanol.
5. The method for preparing a S-doped Co3O4 graphene oxide composite material according to claim 1, characterized in that: In step S2: the mass ratio of the S-Co3O4 nanocrystals to graphene oxide is 2.5:1-3.5:
1.
6. A S-doped Co3O4 graphene oxide composite material prepared according to the preparation method of the S-doped Co3O4 graphene oxide composite material according to any one of claims 1 to 5.
7. A method for preparing a detection electrode, characterized in that: The S-doped Co3O4 graphene oxide composite material according to claim 6 is dispersed in deionized water to form an S-Co3O4 nanocomposite suspension, the S-Co3O4 nanocomposite suspension is placed at the center of a glassy carbon electrode, the glassy carbon electrode is dried, and the S-Co3O4 nanocomposite adheres to the surface of the glassy carbon electrode to obtain the detection electrode.
8. The method for preparing a detection electrode according to claim 7, characterized in that: The glassy carbon electrode is polished with alumina powder, then washed with deionized water, and then dried and added with S-Co3O4 nanocomposite suspension; the amount of S-Co3O4 nanocomposite suspension added is 1 mm 2 Add 1-1.2 μL to the electrode.
9. A detection electrode prepared by the method for preparing a detection electrode according to claim 7.
10. The detection electrode according to claim 9 is used to detect the concentration of arsenic ions in a water environment.
Citation Information
Patent Citations
Mn-doped Co3O4-porous graphene lithium ion battery negative electrode material and preparation method thereof
CN111584869A
Fe3O4-rGO electrochemical sensor as well as preparation method and application thereof
CN113237930A
Preparation method of iron-doped cobaltosic oxide electrode and arsenic-polluted water treatment method
CN115445619A